Experimental transmission of Zika virus by Aedes japonicus japonicus from southwestern Germany. Issue 1 (December 2018) - Jansen, Stephanie; Heitmann, Anna; Lühken, Renke; Jöst, Hanna; Helms, Michelle; Vapalahti, Olli; Schmidt-Chanasit, Jonas; Tannich, Egbert
Abstract The invasive mosquito speciesAedes japonicus japonicus (Ae. japonicus ) is widely distributed in Central Europe and is a known vector of various arboviruses in the laboratory, including flaviviruses such as Japanese Encephalitis virus or West Nile virus. However, the vector competence ofAe. japonicus for the recently emerging Zika virus (ZIKV) has not been determined. Therefore, field-caughtAe. japonicus from Germany were orally infected with ZIKV and incubated at 21, 24, or 27 °C to evaluate the vector competence under climate conditions representative of the temperate regions (21 °C) in the species' main distribution area in Europe and of Mediterranean regions (27 °C).Aedes japonicus was susceptible to ZIKV at all temperatures, showing infection rates between 10.0% (21 °C) and 66.7% (27 °C). However, virus transmission was detected exclusively at 27 °C with a transmission rate of 14.3% and a transmission efficiency of 9.5%. Taking into account the present distribution ofAe. japonicus in the temperate regions of Central Europe, the risk of ZIKV transmission by the studiedAe. japonicus population in Central Europe has to be considered as low. Nevertheless, due to the species' vector competence for ZIKV and other mosquito-borne viruses, in combination with the possibility of further spread to Mediterranean regions, Ae. japonicus must be kept in mind as a potential vector of pathogens inside and outside of Europe.